Implementation of clinical practice guidelines on lifestyle interventions in Swedish primary healthcare - a two-year follow up - Therese Kardakis; Lars Jerdén; Monica E. Nyström; Lars Weinehall; Helene Johansson (BMC, 2018)
Abstract Background Implementation of interventions concerning prevention and health promotion in health care has faced particular challenges resulting in a low frequency and quality of these services. In November 2011, the Swedish National Board of Health and Welfare released national clinical practice guidelines to counteract patients' unhealthy lifestyle habits. Drawing on the results of a previous study as a point of departure, the aim of this two-year follow up was to assess the progress of work with lifestyle interventions in primary healthcare as well as the uptake and usage of the new guidelines on lifestyle interventions in clinical practice. Methods Longitudinal study among health professionals with survey at baseline and 2 years later. Development over time and differences between professional groups were calculated with Pearson chi-square test. Results Eighteen percent of the physicians reported to use the clinical practice guidelines, compared to 58% of the nurses. Nurses were also more likely to consider them as a support in their work than physicians did. Over time, health professionals usage of methods to change patients' tobacco habits and hazardous use of alcohol had increased, and the nurses worked to a higher extent than before with all four lifestyles. Knowledge on methods for lifestyle change was generally high; however, there was room for improvement concerning methods on alcohol, unhealthy eating and counselling. Forty-one percent reported to possess thorough knowledge of counselling skills. Conclusions Even if the uptake and usage of the CPGs on lifestyle interventions so far is low, the participants reported more frequent counselling on patients' lifestyle changes concerning use of tobacco and hazardous use of alcohol. However, these findings should be evaluated acknowledging the possibility of selection bias in favour of health promotion and lifestyle guidance, and the loss of one study site in the follow up. Furthermore, this study indicates important differences in physicians and nurses' attitudes to and use of the guidelines, where the nurses reported working to a higher extent with all four lifestyles compared to the first study. These findings suggest further investigations on the implementation process in clinical practice, and the physicians' uptake and use of the CPGs.